Perception of cigarette smoking in young people from the University of Cauca (Impetus, 2021)
The research sought to identify the perception of cigarette smoking in young people from the University of Cauca. The methodology used was qualitative, through in-depth guided interviews and discussions with 12 university students, 6 men and 6 women with averages of age of 17.5 years, during the year 2013; methods that allowed assessing socio-demographic aspects and personal information about the start and habit of smoking. Within the results found, it was possible to identify that cigarette smoking occurs at an early age specifically during the school phase, in the last levels high school and is accentuated in college, expanding in the latter the possibility of acquiring other stimulating substances. Cigarette smoking is manifested due to social pressures, for symbolic value that represents before his equals his maturity, the feeling of being adults and sometimes "being rebellious before the norms of society ”as well as a way to maintain the ideal weight, reaching the conclusion that the decision to smoke is strongly related to the first contact experiences of these habits. The tendency of ingestion is related to gender, with men more pressured to consume, and the ease of getting these substances with friends or in legal settings such as supermarkets, tobacconists and shops.